Is Brand Image Overrated? A Case Study of New Balance Consumer Behavior in Pekanbaru, Indonesia - Saputra, Eko; Nursanti, Aida; Siregar, Prima Andreas; Noviasari, Henni (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aimed to determine the influence of brand image, product quality, and price on purchasing decisions for New Balance shoes in Pekanbaru. The population in this study consisted of all Pekanbaru residents who used New Balance shoes. The sample size in this study was determined using the purposive sampling technique, in which all New Balance shoe users were included in the sample, resulting in a total of 105 respondents. The data analysis method used in this research was multiple linear regression analysis, processed using SPSS version 31. The results show that brand image has no significant influence on purchasing decisions. Product quality significantly influences purchasing decisions. Price significantly influences purchasing decisions. Brand image, product quality, and price significantly influence purchasing decisions.